Boosting reading skill in Narrative texts with Question Answer Relationship (QAR) - Aldiansya, Febri; Mansour, Marwa (Indonesian Journal of Multidisciplinary Educational Research, 2025)
This study sought to determine whether the Question Answer Relationship (QAR) technique may increase students' reading comprehension of narrative literature. The research design employed in this study is Classroom Action Research (CAR). The research is carried out in a single cycle, which includes planning, acting, observation, and reflection. The participants in this study were ninth-grade students at a state junior high school in Kediri. The researcher collected the data by observation, testing, and documentation. The results of this study showed that the Question Answer Relationship technique improved ninth-grade students' comprehension of narrative written works. The results from the students' mean or average performance on the pre- and post-tests for cycle 1 support this. Cycle 1's average post-test score was 79.44, up from a mean pre-test score of 56.52. The findings of this study indicate that the Question Answer Relationship (QAR) Strategy was helpful in improving students' reading comprehension of narrative content.